Severe Allergic Bronchopulmonary Mycosis and Long-Term Follow-Up - Hossein Esmaeilzadeh; Sara Kashef; Hamid Reza Hatami; Soheila Alyasin; Hesamodin Nabavizadeh; Elmira Esmaeilzadeh (Case Reports in Immunology)
Allergic bronchopulmonary aspergillosis (ABPA) is the most common immunologic reaction following fungal allergen exposure in asthmatic patients. A less frequent syndrome in response to other fungal species like candida is allergic bronchopulmonary mycosis (ABPM). This reaction is mostly associated with asthma exacerbation, changes in Immunoglobulin E levels, and nonspecific findings in high resolution computed tomography (HRCT). This study presents a 9-year-old girl, a known case of childhood asthma, resolved 4 years ago as a novel case of ABPM due to Candida albicans manifested by severe emphysema, bronchiectasis, and pneumothorax which consequently required long-term treatment to get relieved.